Records Management Practices of Barangay STO. Domingo, Nabua, Camarines Sur, Philippines - Agapito, Abegail F.; Hallare, Syrell M.; Lal, Julie Ann P.; Metran, Rose Ann O. (Jurnal Genesis Indonesia, 2025)
This study aimed to evaluate the current status and identify the challenges faced in the records management practices of a barangay in Nabua, Camarines Sur, focusing on four key areas: records creation, maintenance, retention, and disposition. It also examined the significant relationship between existing records management practices and the problems encountered by respondents, and proposed recommendations to enhance current practices. A descriptive-correlational survey method was employed to collect, analyze, and interpret data, utilizing physical questionnaires. The data were analyzed using methods such as the Likert scale, weighted mean, and Kendall’s Tau correlation. Of the 27 distributed questionnaires, 22 were retrieved and included in the analysis. Findings indicated that while Barangay Sto. Domingo in Nabua, Camarines Sur had established basic records management practices, respondents frequently encountered issues across all four areas of records management: creation, maintenance, retention, and disposition.